Mammographic density and breast cancer in women from high risk families. Issue 1 (December 2015) - Ramón y Cajal, Teresa; Chirivella, Isabel; Miranda, Josefa; Teule, Alexandre; Izquierdo, Ángel; Balmaña, Judith; Sánchez-Heras, Ana; Llort, Gemma; Fisas, David; Lope, Virginia; Hernández-Agudo, Elena; Juan-Fita, María; et al.
Abstract Introduction Mammographic density (MD) is one of the strongest determinants of sporadic breast cancer (BC). In this study, we compared MD inBRCA1/2 mutation carriers and non-carriers fromBRCA1/2 mutation-positive families and investigated the association between MD and BC amongBRCA1/2 mutation carriers per type of mutation and tumor subtype. Methods The study was carried out in 1039 female members ofBRCA1 andBRCA2 mutation-positive families followed at 16 Spanish Genetic Counseling Units. Participants' density was scored retrospectively from available mammograms by a single blinded radiologist using a 5-category scale (<10 %, 10-25 %, 25-50 %, 50-75 %, >75 %). In BC cases, we selected mammograms taken prior to diagnosis or from the contralateral breast, whereas, in non-cases, the last screening mammogram was evaluated. MD distribution in carriers and non-carriers was compared using ordinal logistic models, and the association between MD and BC inBRCA1/2 mutation carriers was studied using logistic regression. Huber-White robust estimators of variance were used to take into account correlations between family members. A similar multinomial model was used to explore this association by BC subtype. Results We identified and scored mammograms from 341BRCA1, 350BRCA2 mutation carriers and 229 non-carriers. Compared to non-carriers, MD was significantly lower amongBRCA2 mutation carriers (odds ratio (OR) =0.71;P- value=0.04), but not amongBRCA1 carriers (OR=0.84;P- value=0.33). MD was associated with subsequent development BC (OR per category of MD=1.45; 95 % confidence interval=1.18-1.78, P- value<0.001), with no significant differences betweenBRCA1 andBRCA2 mutation carriers (P- value=0.48). Finally, no statistically significant differences were observed in the association of MD with specific BC subtypes. Conclusions Our study, the largest to date on this issue, confirms that MD is an independent risk factor for all BC subtypes in eitherBRCA1 andBRCA2 mutation carriers, and should be considered a phenotype risk marker in this context.